Solve the equation with the quadratic formula `x_(1,2)=(-bpm sqrt(b^2-4ac))/(2a)`  and check the answer.

`4b^2+5=10b`

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Let's first write the equation in standard form, that is everything on the left and only 0 on the right hand side.

`4b^2-10b+5=0`

Now we only need to put coefficients of this equation into quadratic formula where `a=4` (coefficient by the power 2), `b=-10` (linear coefficient) and `c=5` (free coefficient). Hence we have

`b_(1,2)=(-(-10)pm sqrt((-10)^2-4cdot4cdot5))/(2cdot4)=(10pm sqrt(100-80))/(8)=(10pm sqrt(20))/8=`

`(10pm2sqrt(5))/8=(5pm sqrt5)/4`

`b_1=(5-sqrt5)/4`  <-- First solution

`b_2=(5+sqrt5)/4`  <-- Second solution

To check our solutions we simply put them into our equation instead of `b.` So for `b_1` we have

`4((5-sqrt5)/4)^2-10cdot(5-sqrt5)/4+5=4cdot(25-10sqrt5+5)/16-(5(5-sqrt5))/2+5=`

`(30-10sqrt5)/4-(25-5sqrt5)/2+5=(15-5sqrt5)/2-(25-5sqrt5)/2+5=`

`(15-5sqrt5-25+5sqrt5)/2+5=-10/2+5=-5+5=0`

So if we put `b_1` instead of `b` into our equation we get 0 what we were supposed to get because on the right hand side we have 0. Similarly for `b_2` we have

`4((5+sqrt5)/4)^2-10cdot(5+sqrt5)/4+5=(30+10sqrt5)/4-(25+5sqrt5)/2+5=`

`(15+5sqrt5-25-5sqrt5)/2+5=-10/2+5=-5+5=0`

Which confirms that `b_2` is solution of our equation.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial